Ngalayad Dan Kebatan: Korelasi Tradisi Budaya Sunda Dengan Kewajiban Seorang Muslim Dalam Bertetangga - Muhamad Parhan; Deni Abdul Ghoni; Hanipa Nurul Nisa; Mah Kimkim (Purwadita : Jurnal Agama dan Budaya, 2021)
This research is motivated by community unrest towards culture which is considered idolatrous and bid'ah. The tradition of mourning and giving money or food for a bereaved family is still in the crew, whether or not it is allowed. Seeing this problems, it is necessary to study this phenomenon by taking an example of a tradition related to this problem, one of which is the tradition of ngalayad and kebatan which is inherent in Sundanese life. This study aims to analyze: 1) ngalayad tradition in Sundanese culture, 2) kebatan tradition in Sundanese culture; describes 1) the obligations of Muslims in neighboring life related to the traditions of Ngalayad and kebatan, and 2) maintaining culture and religion in the tradition of Ngalayad and kebatan. To achieve these objectives, the research used in qualitative-descriptive research methods with literature study techniques. The results of this study obtained data and the fact that religion really appreciates the activity of mourning/takziah and giving food or money to a bereaved family as a means of giving alms to ease the burden and comfort the grieving family. Keywords: kebatan; neighboring obligations; ngalayad.